Analysis Of Physical Components On The Sila Football Abilities Of The Sepak Takraw Game Of Pra Pon Sulsel Athletes - Suriah Hanafi; Achmad Karim (Journal Physical Health Recreation (JPHR), 2023)
This study aims to prove: 1) The relationship between the speed of foot reaction and the ability to take kicks in the sepak takraw game, 2) The relationship between balance and the ability to kick the kick in the kickball game, 3) The relationship between speed Foot reaction and balance on the ability of Sila in the game of takraw. The research method used is a quantitative research method and this type of research is a correlational study involving 2 independent variables, namely the speed of foot reactions and balance, while the dependent variable is the ability to kick Silat in the game of takraw. The population in this study were athlete Pra PON SULSEL, with a sample of 30 people taken by simple random sampling. The data analysis technique used is the correlation coefficient. The results of the research conducted showed that: 1) There is a significant relationship between the speed of foot reaction and the ability to kick in the takraw game with a value of r = 0.867 (p <ɑ0.05). 2) There is a significant relationship between the balance and the ability to play sila in the game of takraw r = 0.792 (p <ɑ0.05). 3) There is a significant relationship between the speed of foot reaction and balance together with the ability to take part in the kick takraw game by 78.8% with a value of R = 0.888 (p<ɑ0.05).